2021
DOI: 10.3389/fneur.2021.742567
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Repetitive Transcranial Magnetic Stimulation for Acute Central Post-stroke Pain: A Case Study

Abstract: Although rare, central post-stroke pain remains one of the most refractory forms of neuropathic pain. Repetitive transcranial magnetic stimulation (rTMS) has been reported to be effective in chronic cases. However, there are no data on the effects in the acute and subacute phases after stroke. In this study, we present a case of a patient with thalamic stroke with acute onset of pain and paresthesia who was responsive to rTMS. After a right thalamic stroke, a 32-year-old woman presented with drug-resistant pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…In addition, most studies suggest that the possible cause of CPSP is central de-inhibition or central imbalance due to ischemia ( Ri, 2022 ), then restoration of abnormal cortical excitability by TMS may be one of the potential mechanisms for the relief of recalcitrant CPSP. As found in the study, 10 Hz HF-rTMS had significant analgesic effects in CPSP patients in all periods, and M1 HF-rTMS had better analgesic effects than M1 LF-rTMS ( Leung et al, 2020 ; Malfitano et al, 2021 ). This suggests that in patients with CPSP, increasing cortical excitability in the lesioned hemisphere is far more effective than inhibiting cortical excitability in the unlesioned hemisphere, after all, the imbalance in the regulation of downstream somatosensory pathways due to reduced cortical excitability in the lesioned hemisphere is the most direct cause of CPSP.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, most studies suggest that the possible cause of CPSP is central de-inhibition or central imbalance due to ischemia ( Ri, 2022 ), then restoration of abnormal cortical excitability by TMS may be one of the potential mechanisms for the relief of recalcitrant CPSP. As found in the study, 10 Hz HF-rTMS had significant analgesic effects in CPSP patients in all periods, and M1 HF-rTMS had better analgesic effects than M1 LF-rTMS ( Leung et al, 2020 ; Malfitano et al, 2021 ). This suggests that in patients with CPSP, increasing cortical excitability in the lesioned hemisphere is far more effective than inhibiting cortical excitability in the unlesioned hemisphere, after all, the imbalance in the regulation of downstream somatosensory pathways due to reduced cortical excitability in the lesioned hemisphere is the most direct cause of CPSP.…”
Section: Introductionsupporting
confidence: 79%
“…Currently, CPSP is mainly treated with pharmacological agents, such as anticonvulsants, which have good effects on improving the symptoms of CPSP ( Bo et al, 2022 ), but when it comes to intractable CPSP, the drugs may only play the role of placebo and do not provide a good solution to the patient’s CPSP troubles. A recent study found that rTMS in the cerebral motor cortex had a significant effect on relieving recalcitrant CPSP ( Malfitano et al, 2021 ), but the duration varied, which may be related to the site of ischemia, the period of disease progression, the site of stimulation, and individual patient differences. Therefore, there is a need to explore the therapeutic parameters related to the improvement of CPSP by TMS.…”
Section: Introductionmentioning
confidence: 99%
“…In a case study, 10 Hz rTMS was applied to the M1 site of a subacute CPSP patient for 2,000 pulses each time, with an intensity of 90% of RMT, for a total of 10 sessions, and the pain levels were measured before, after stimulation, and 1 month after stimulation. The results showed that the level of post-stimulation was significantly lower than the baseline level, suggesting that rTMS had the same analgesic effect on acute CPSP (Malfitano et al, 2021).…”
Section: Rtms Has Analgesic E Ects On Various Types Of Painmentioning
confidence: 88%
“…Short-term analgesia was produced by targeted stimulation of S2 and M1, but the results were no different than those in the placebo group, demonstrating a potent placebo effect [ 100 ]. Table 4 contains additional in-depth research concerning the influence of rTMS on CPSP [ 101 103 ].…”
Section: Main Bodymentioning
confidence: 99%